Active matrix metalloproteinase‐8 and periodontal bacteria—interlink between periodontitis and inflammatory bowel disease?. Issue 6 (10th July 2018) - Schmidt, J.; Weigert, M.; Leuschner, C.; Hartmann, H.; Raddatz, D.; Haak, R.; Mausberg, R.F.; Kottmann, T.; Schmalz, G.; Ziebolz, D.
Abstract: Background: The aim of this study was the investigation of concentration and prevalence of selected periodontal pathogenic bacteria and concentration of active matrix metalloproteinase‐8 (aMMP‐8) within a group of patients with inflammatory bowel diseases (IBD) and to compare the results with a group of healthy control subjects (HC). Methods: Fifty‐nine IBD patients with Crohn`s disease (CD, n = 30) or ulcerative colitis (UC, n = 29) and 59 HC were included in this cross‐sectional study. Based on periodontal probing depth (PD) and clinical attachment level (CAL), periodontitis was classified as healthy/mild, moderate, or severe. aMMP‐8 was analyzed from gingival crevicular fluid using enzyme linked immunosorbent assay. Eleven selected periodontal pathogenic bacteria were analyzed in subgingival plaque samples using polymerase chain reaction. Results: IBD patients showed higher CAL ( P < 0.01), more severe periodontitis ( P = 0.04), gingival bleeding ( P < 0.01) and aMMP‐8 concentration ( P < 0.01) than HC. Only in CD, increasing severity of periodontitis was associated with an increase in aMMP‐8 concentration ( P = 0.02). The prevalences of Eubacterium nodatum and Eikenella corrodens were significantly lower in IBD compared to HC ( P = 0.01). Additionally, the prevalence of Eikenella corrodens was significantly higher in CD compared to the UC group ( P = 0.04). Further statistically significant differences in selected bacteria between IBD and HC or CD and UC groups could not be found ( P > 0.05). Conclusions: The results reveal changes in host immune response of IBD patients in terms of aMMP‐8. Only in CD increasing aMMP‐8 was associated with severity of periodontal disease. The role of periodontal pathogenic bacteria in the interrelationship between IBD and periodontitis remains unclear.